2018
DOI: 10.3390/molecules23040806
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucans: Multi-Functional Modulator of Wound Healing

Abstract: β-glucans are derived from a variety of sources including yeast, grain and fungus and belong to the class of drugs known as biological response modifiers. They possess a broad spectrum of biological activities that enhance immunity in humans. One promising area for β-glucans’ application is dermatology, including wound care. Topical applications of β-glucans are increasing, especially due to their pluripotent properties. Macrophages, keratinocytes and fibroblasts are considered the main target cells of β-gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 61 publications
1
64
0
Order By: Relevance
“…In any case, the most significant stimulus to cell viability came from CGJ3 both after 24 and 48 h (336.7% and 351.7%, respectively). In agreement with a previous report showing that β-glucans promote cell proliferation in different cell types [34], this biochemical behavior could be due to the higher number of β-glucans in CGJ3 fraction (Table 4) if compared to CGJ1 and CGJ2. Similar proliferative effects were observed for HaCaT cells treated with the corresponding soluble glucans SGJ1, SGJ2, and SGJ3 ( Figure 7).…”
Section: Cell Viabilitysupporting
confidence: 93%
“…In any case, the most significant stimulus to cell viability came from CGJ3 both after 24 and 48 h (336.7% and 351.7%, respectively). In agreement with a previous report showing that β-glucans promote cell proliferation in different cell types [34], this biochemical behavior could be due to the higher number of β-glucans in CGJ3 fraction (Table 4) if compared to CGJ1 and CGJ2. Similar proliferative effects were observed for HaCaT cells treated with the corresponding soluble glucans SGJ1, SGJ2, and SGJ3 ( Figure 7).…”
Section: Cell Viabilitysupporting
confidence: 93%
“…Sargassum ilicifolium aqueous extracts were also reported to engender an enhanced wound closure rate (97.83%) in L929 cells at 24 h compared with the rate observed in control cells (46.11%); hence, the wound closure rate of the treated cells was higher than that of the control cells by 112.17% [31], indicating PNPs demonstrated better enhancement in fibroblast migration. It was indicated that β-glucans are a multi-functional modulator of wound healing [54], for instance, (1→3)-(1→6)-β-D-glucan from Aureobasidium pullulans stimulates dermal fibroblast proliferation and migration [55]. Moreover, our previous study showed that the β-D-glucan contents in PNP-40, PNP-60 and PNP-80 were 20.20%, 12.20% and 10.15%, respectively [16], and other report was indicated as a β-D-glucan-(1→3)-linked, substituted at O-6 by β-D-Glcp or (1→6)-linked β-D-Glcp side chains using NMR and methylation analyses [56], suggesting that β-d-glucan might be one of active substances in PNPs elevating cell migration and proliferation.…”
Section: Cell Proliferation and Migrationmentioning
confidence: 99%
“…Macrophages, keratinocytes and fibroblasts are considered the main target cells of β-glucans during wound healing. β-glucans enhance wound repair by increasing the infiltration of macrophages, which stimulates tissue granulation, collagen deposition and re-epithelialization [157]. A long-term use of glucan showed reduction of wrinkle depth, height and overall roughness, which is probably caused by stimulation of fibroblast and increase production of collagen.…”
Section: G α-Lipoic Acidmentioning
confidence: 99%